Variability of professional soccer players` perceived match load after successive matches - Azcárate, U.; Los Arcos, A.; Yanci, J. (Research in Sports Medicine, 2021)
This study analyses the differential perceived match load accumulated by professional soccer players depending on their: (a) participation in several consecutive official matches within the same week (Pre_Cup, Cup, and Post_Cup), and (b) total match participation time (i.e. 90min, 70-90min and < 70min). Participants were 21 Spanish Second Division professional soccer players (M age=27.1, SD=3.3years; M body height=182.1, SD=3.9 cm; M body mass=75.8, SD=5.14 kg). There were no significant differences (p >0.05) in dRPE-ML among Pre_Cup, Cup and Post_Cup matches or in dRPE-ML between teams that took part in two or three official matches within the same week or three official matches in 2-4 consecutive weeks. The results suggest that participating in several matches in the same week does not increase accumulated perceived exertion for professional soccer players.